Teacher guide: implementing the CEFR-aligned curriculum: planning and managing learning (second edition) - Abdul Latif @ Bapoo, Lilisuriani (Kementerian Pendidikan Malaysia, 2020)
This guide is designed to help teachers develop their own lesson plans and activities using the CEFR-aligned Curriculum Framework, Syllabus, and Scheme of Work as references. The content is drawn from the resource materials provided by Cambridge English (CE) at the CEFR Familiarisation, Learning Materials Adaptation (LMA), Curriculum Assessment (FA) training sessions that teachers have been through.